UPBEAT-UK: a programme of research into the relationship between coronary heart disease and depression in primary care patients - André Tylee; Elizabeth A Barley; Paul Walters; Evanthia Achilla; Rohan Borschmann; Morven Leese; Paul McCrone; Jorge Palacios; Alison Smith; Rosemary Simmonds; Diana Rose; Joanna Murray; et al. (NIHR Journals Library, 2016)
Background: Depression is common in patients with coronary heart disease (CHD) but the relationship is uncertain. In the UK, general practitioners (GPs) have been remunerated for finding depression in CHD patients; however, it is unclear how to manage these patients. Objectives: Our aim was to explore the relationship between CHD and depression in a GP population and to develop nurse-led personalised care (PC) for patients with CHD and depression. Design: The UPBEAT-UK study consisted of four related studies. A cohort study of patients from CHD registers to explore the relationship between CHD and depression. A metasynthesis of relevant literature and two qualitative studies [patients' perspectives and GP/practice nurse (PN) views on management of CHD and depression] helped develop an intervention. A pilot randomised controlled trial (RCT) of PC was conducted. Setting: Thirty-three GP surgeries in south London. Participants: Adult patients on GP CHD registers. Interventions: From the qualitative studies, we developed nurse-led PC, combining case management and self-management theory. Following biopsychosocial assessment, a PC plan was devised for each patient with chest pain and depressive symptoms. Nurses helped patients address their most important related problems. Use of existing resources was promoted. Nurse time was conserved through telephone follow-up. Main outcome measures: The main outcome of the pilot study of our newly developed PC for people with depression and CHD was to assess the acceptability and feasibility of the intervention and to decide on the best outcome measures. Depression, measured by the Hospital Anxiety and Depression Scale - depression subscale, and chest pain, measured by the Rose angina questionnaire, were the main outcome measures for the feasibility and cohort studies. Cardiac outcomes in the cohort study included: attendance at rapid access chest pain clinics, stent insertion, bypass graft surgery, myocardial infarction and cardiovascular death. Service use and costs were measured and linked to quality-adjusted life-years (QALYs). Data for the pilot RCT were obtained by research assistants from patient interviews at baseline, 1, 6 and 12 months for the pilot RCT and at baseline and 6-monthly interviews for up to 36 months for the cohort study, using standard questionnaires. Results: Personalised care was acceptable to patients and proved feasible. The reporting of chest pain in the intervention group was half that of the control group at 6 months, and this reduction was maintained at 1 year. There was also a small improvement in self-efficacy measures in the intervention group at 12 months. Anxiety was more prevalent than depression in our CHD cohort over the 3 years. Nearly half of the cohort complained of chest pain at outset, with two-thirds of these being suggestive of angina. Baseline exertional chest pain (suggestive of angina), anxiety and depression were independent predictors of adverse cardiac outcome. Psychosocial factors predicted the continued reporting of exertional chest pain across the 3 years of follow-up. Costs were slightly lower for the PC group but QALYs were also lower. Neither difference was statistically significant. Conclusions: Chest pain, anxiety, depression and social problems are common in patients on CHD registers in primary care and predict adverse cardiac outcomes. Together they pose a complex management problem for GPs and PNs. Our pilot trial of PC suggests a promising approach for treatment of these patients. Generalisation is limited because of the selection bias in recruitment of the practices and the subsequent participation rate of the CHD register patients, and the fact that the research took place in south London boroughs. Future work should explicitly explore methods for effective implementation of the intervention, including staff training needs and changes to practice. Trial registration: Current Controlled Trials ISRCTN21615909. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 4, No. 8. See the NIHR Journals Library website for further project information.